Treatment of high risk ET – data from the EXELS study. (May 2016) - Birgegård, G.; Besses, C.; Griesshammer, M.; Gugliotta, L.; Harrison, C.; Hamdani, M.; Achenbach, H.; Kiladjian, J.-J.
Abstract: Background: The Evaluation of Xagrid Efficacy and Long-term Safety (EXELS) study (NCT00567502) is the largest prospective observational cohort of high-risk patients with essential thrombocythemia (ET) reported to date. Objectives: The primary objective were safety and pregnancy outcomes of anagrelide (ANA) compared with other cytoreductive therapies (CRT). Secondary objectives included efficacy, measured by the incidence of thrombohemorrhagic events and platelet reduction. Methods: High-risk patients (≥1 of age >60 years, previous thrombotic event, platelet count >1000 × 10 9 /L) with ET were enrolled across 13 countries in Europe between 2005 and 2009. Pts were required to be receiving CRT. Data, including events predefined in the protocol (PDEs), were collected every 6 months for 5 years for all patients. Event rates are presented as number of patients per 100 patient-years exposure and by treatment at time of event. Event rates are provided rather than p values due to the observational nature of the study. Preliminary final data are presented and final data, including platelet response and pregnancy results, will be available at ASH. Recently, results have remained stable and conclusions are not expected to change. Results: 3649 patients were categorized according to treatment at registration as follows: ANA (n=804), ANA + other CRT (n=141), other CRT (n=2666) and no CRT (n=38). Over 80% of patients received either hydroxycarbamide (HC) or ANA, and 69.8% of patients received antiaggregatory therapy. At registration, median age was lower in the ANA (55.5 years, range 18–89) and ANA + other CRT (59.0 years, range 22–88) groups vs the other CRT group (70.0 years, range 17–95). The arterial thrombotic event rate was similar in ANA (1.63) and other CRT (1.62) groups, whereas venous thrombotic event rates differed (0.35 vs 0.57). The major hemorrhagic event rate was highest in the ANA group, especially in patients also treated with anti-aggregatory therapy (1.24). 105 patients transformed to myelofibrosis (MF) and 62 to acute leukemia (AL). Transformation to MF rates were similar in the ANA (1.31) and ANA + other CRT (1.27) groups, but lower in the other CRT (0.32) group. Rate of transformation to AL was 0.17, 0.46, and 0.33, respectively. In patients who had only ever received either ANA or HC, rate of transformation to MF was higher in the ANA vs HC group (0.78 vs 0.17) whereas transformation to AL was higher in the HC vs ANA group (0.22 vs 0). All patients who ever received ANA and transformed to AL had also received prior HC. PDEs of greatest interest are displayed in Table 1. Non-hematological malignancy was the most frequent PDE in the other CRT group. 57.4% of deaths were attributed to a PDE; transformation (event rate, 1.9), most frequently to AL (1.3), and non-hematological malignancies (1.6) were the most frequent causes of PDE-related death. No unexpected side effects were noted. There were 54 pregnancies, of which 41 were successful (76%). The proportion of patients with a white blood cell (WBC) count >15 × 10 9 /L at any time was higher in patients who died (12.5%) vs alive patients (6.1%) and in patients who had transformed (15.7%) vs those who did not transform (5.7%). Conclusion: Patients receiving ANA were younger than those receiving other CRT. Thrombotic event rates were low; arterial events were similar between ANA and other CRT groups, and venous events were lower in the ANA vs other CRT group. Hemorrhage was most frequent in the ANA + anti-aggregatory therapy group, whereas non-hematological malignancy was most frequent in the other CRT group. Transformation to MF was more frequent in the ANA group, whereas transformation to AL was more frequent in the HC group. The incidence of death and transformation was higher in patients with a WBC count >15 × 10 9 /L.